2015
DOI: 10.1007/s11104-015-2612-4
|View full text |Cite
|
Sign up to set email alerts
|

Wheat roots efflux a diverse array of organic N compounds and are highly proficient at their recapture

Abstract: Background & aims Small organic N compounds could contribute to N nutrition, but an alternative view is that root uptake may serve to recapture compounds that efflux out of roots. However, it is unclear if plants can recapture leaked organic N compounds because no studies have examined quantitative relationships between efflux and uptake at sub-micromolar concentrations. Methods This study examines efflux and uptake of a broad suite of small organic N compounds by wheat (Triticum aestivum L.).15 N-labeling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 61 publications
(99 reference statements)
8
51
0
Order By: Relevance
“…Many metabolites (defined here as organic compounds less than 1000 Da) have been reported from root exudates including sugars, amino acids, organic acids, lipids, phenolics and other secondary metabolites (Flores et al 1999;Dakora and Phillips 2002;Jones et al 2003;Read et al 2003;Walker et al 2003;Badri and Vivanco 2009;Chaparro et al 2013;Strehmel et al 2014), and high molecular weight metabolites such as polysaccharides and proteins (Walker et al 2003). In recent years the application of untargeted mass spectrometry-based methods has built on previous work and uncovered an even larger number and diversity of metabolites in root exudates (Strehmel et al 2014;Warren 2015). For example, capillary electrophoresismass spectrometry of exudates of wheat detected 110 organic N metabolites and found that while amino acids were abundant, they accounted for less than half of the organic N in root exudates (Warren 2015).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many metabolites (defined here as organic compounds less than 1000 Da) have been reported from root exudates including sugars, amino acids, organic acids, lipids, phenolics and other secondary metabolites (Flores et al 1999;Dakora and Phillips 2002;Jones et al 2003;Read et al 2003;Walker et al 2003;Badri and Vivanco 2009;Chaparro et al 2013;Strehmel et al 2014), and high molecular weight metabolites such as polysaccharides and proteins (Walker et al 2003). In recent years the application of untargeted mass spectrometry-based methods has built on previous work and uncovered an even larger number and diversity of metabolites in root exudates (Strehmel et al 2014;Warren 2015). For example, capillary electrophoresismass spectrometry of exudates of wheat detected 110 organic N metabolites and found that while amino acids were abundant, they accounted for less than half of the organic N in root exudates (Warren 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the application of untargeted mass spectrometry-based methods has built on previous work and uncovered an even larger number and diversity of metabolites in root exudates (Strehmel et al 2014;Warren 2015). For example, capillary electrophoresismass spectrometry of exudates of wheat detected 110 organic N metabolites and found that while amino acids were abundant, they accounted for less than half of the organic N in root exudates (Warren 2015). These recent studies have identified an impressive number of metabolites, but have not been especially comprehensive.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations